A Framework for Problem Formulation in Climate Change Issues: Formulating Policy Recommendations Using Energy Indicators for Sustainable Development - Rizky Dwi Lestari; Renata Jati Nirmala (Departemen Administrasi Publik, Universitas Diponegoro, 2023)
This paper aims to explore the application of William Dunn's framework for problem formulation in the context of addressing climate change issues. The study focuses on formulating policy recommendations by utilizing energy indicators within a sustainable development framework. The objective is to assess two potential policy options: Local Technology Innovation with Public-Private Partnership (PPP) Scheme and Model Energy as a Service. By employing Dunn's framework, the paper provides an in-depth explanation of its utilization during the problem formulation phase. This framework offers a systematic approach to understanding and defining complex problems, such as climate change, by considering various perspectives, stakeholders, and causal factors involved. The paper then proceeds to apply the framework to the climate change issue, specifically by incorporating energy indicators within a sustainable development context. The findings of this study contribute to the ongoing discourse on climate change policy formulation and provide insights into the practical application of Dunn's framework. The policy recommendations derived from this research can assist policymakers, stakeholders, and practitioners in making informed decisions and shaping effective strategies for addressing climate change while advancing sustainable development goals.